2022
DOI: 10.3389/fmed.2022.811746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Patients Important Outcomes in Older People With Sarcopenia: An Umbrella Review of Meta-Analyses of Randomized Controlled Trials

Abstract: BackgroundMany clinical practice guidelines strongly recommend exercise as an intervention for patients with sarcopenia. However, the significance of exercise on patient-important outcomes in older adults with sarcopenia is inconsistent when considering available minimal important differences. To synthesize current systematic review and meta-analyses evidence on the efficacy of exercise on patient-important outcomes in the treatment of sarcopenia in older adults.MethodsWe searched MEDLINE, EMBASE, Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Both the Asian Working Group for Sarcopenia Standards (AWGS) and the 2nd Edition of the European Working Group on Sarcopenia Standards (EWGSOP2) include walking speed as the diagnosis criteria of sarcopenia. The results of this study confirm that exercise can effectively increase the walking speed of the target group, which is consistent with previous studies [61][62][63]. However, a relatively higher level of heterogeneity existed among the included studies.…”
Section: Discussionsupporting
confidence: 91%
“…Both the Asian Working Group for Sarcopenia Standards (AWGS) and the 2nd Edition of the European Working Group on Sarcopenia Standards (EWGSOP2) include walking speed as the diagnosis criteria of sarcopenia. The results of this study confirm that exercise can effectively increase the walking speed of the target group, which is consistent with previous studies [61][62][63]. However, a relatively higher level of heterogeneity existed among the included studies.…”
Section: Discussionsupporting
confidence: 91%
“…There is one large randomized controlled trial (RCT) 26 including 1519 older adults with sarcopenia available but was not included in the two NMAs. Moreover, our team previously conducted an umbrella review of systematic reviews trying to summarize the evidence for exercise as a treatment for sarcopenia and found that the quality of existing systematic reviews was low and, crucially, did not report on quality of life or all‐cause mortality 27 …”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial (RCT) by Otsuka et al (2022) showed that moderate-intensity RE improved the quality and quantity of lower muscle group, such as quadriceps and vastus lateralis muscle, in men and women aged 50-79 years compared with those who did not exercise in the 24 weeks trial. Another study to support the positive effect of exercise on sarcopenia is presented by Shen et al (2022) who concluded that there was an improvement of grip strength, knee extension strength, walking speed, and faster TUG test in sarcopenic patients that implemented exercise intervention. Although RE is considered the first-line treatment of sarcopenia, lower intense exercise also has positive impacts on sarcopenic patients.…”
Section: Overviewmentioning
confidence: 99%